(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Zoonoses are diseases that have claimed millions of lives in both humans and animals. This disease can be transferred from infected animals to humans or vice versa. It has been reported that 75% of zoonotic diseases are emerging. This paper aims to describe various types of emerging and reemerging zoonotic diseases that occur in Indonesia and abroad. Data collection is done online through several websites including the Office International des Epizooties, World Health Organization and the Ministry of Health of the Republic of Indonesia in collaboration with published research reports related to zoonotic diseases. Various disease data were found, both emerging and reemerging. The zoonotic diseases that are endemic and have been reported include COVID-19, avian influenza, swine influenza, dengue, chikungunya, hepatitis E, and rabies. All these diseases occur in Indonesia and throughout the world. Based on the description above, it can be concluded that various types of emerging and reemerging zoonotic diseases occur in Indonesia.